Mortgage selection and consumer confusion in the Malaysian mortgage market - Kosim, Zunarni; Thi, Lip Sam; Tan, Sek-Choo; Ahmad Zawawi, Suryati (2013)
The study aims to investigate the criteria used by mortgage consumers in deciding their mortgage choice. To achieve the objective, questionnaires were distributed to mortgage consumers who took up mortgage between year 2007 to 2011.The results show that consumers perceived interest rate as the most important factor in determining their mortgage choice. However, the lowest interest rate is not the ultimate determinant factor, interest rate be considered in isolation. Consumers also need to take into account the ability to service the monthly repayment and the amount is a function of the loan tenure. Ultimately, the ability to service the monthly repayments would determine the eligibility to obtain a mortgage. Therefore, consumers’ confusion is related to the level of interest rate since interest rate is not the sole determinant of mortgage choice.